(untitled) (SCIENCE TIME JOURNAL, 2026)
This study examines how diverse socioeconomic, racial, and cultural backgrounds influence English as a Foreign Language (EFL) acquisition, proficiency, and fluency. Focusing on a specific case study of a first-year multilingual student group (XTR 1-23) majoring in Foreign Language and Literature at Kokand University, the paper explores the distinct learning behaviors and linguistic variations present within an educational framework predominantly instructed via the Russian language. The group’s profile reveals two primary axes of stratification: ethnicity (the contrasting linguistic hurdles of Uzbek students facing grammatical challenges versus Russian students navigating phonetic/pronunciation barriers) and socioeconomic status (high-income students benefiting from extracurricular tutoring and tech-centric vocabulary versus middle-income students relying on self-study and generalized lexicon).